Kepemimpinan Visioner Dalam Pengembangan Perilaku Organisasi Di Pondok Pesantren Munirul Arifin Nw Praya - Sunardi, Sunardi; Fitriani, Muh Iwan; Imran, Imran (Universitas Hamzanwadi, 2025)
This study describes visionary leadership in developing organizational behavior and culture at Pondok Pesantren Munirul Arifin NW Praya. The research is qualitative in nature, employing a descriptive analysis approach with field research. Data collection techniques included observation, documentation, and interviews.The findings of this study are as follows: 1)The implementation of visionary leadership at Pondok Pesantren Munirul Arifin NW Praya is realized through the application of leadership roles as: Direction setter: The leader has full control over the operational and developmental aspects of the pesantren, Agent of change: The leader is capable of understanding evolving dynamics as a reference for policy-making. Spokesperson: The leader possesses strong communication skills. Coach: The leader engages in job sharing as a form of training. 2) The visionary leadership of the leader at Pondok Pesantren Munirul Arifin NW Praya is relevant to the formation of positive organizational behavior and culture for caregivers/teachers/staff and students in the pesantren. The positive organizational behaviors formed include: understanding the institution's vision and mission, building a solid team, fostering strong solidarity, and maintaining togetherness. The organizational culture established includes: sincerity, sensitivity, simplicity, discipline, and a willingness to learn.